A Pengaruh Komposisi Fiberglass-Epoksi Terhadap Kekuatan Tarik Material Komposit Sebagai Alternatif Rangka E-Scooter (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
Composite materials have the potential to be used as an alternative material for e-scooter frames due to their low weight and good mechanical strength. The mechanical properties of composite materials are strongly influenced by their constituent materials, particularly the fiber fraction. This study aims to analyze the effect of fiberglass composition variations on the tensile strength of composite materials as an alternative for e-scooter frames. The results show that increasing the fiberglass content leads to an improvement in the tensile strength of the composite material. The tensile strength increased by 51.52% when the fiberglass content was increased from 40% to 50%, while an increase of 19.5% was observed from 50% to 60%, indicating a decreasing rate of improvement. At higher fiberglass compositions, voids were observed due to imperfections in the manufacturing process, which affected the bonding between the fiber and the resin. In addition, increasing the fiberglass content resulted in a reduction in tensile strain from 1.1% at 40% fiberglass to 0.55% at 60% fiberglass, indicating that the material became stiffer and more brittle. These results indicate a trade-off between increased tensile strength and reduced ductility of the composite material.